Outcomes of tracheal resection and anastomosis in patients with tracheal stenosis: a clinical perspective - R. Muthukumar; RMahesh Kumari; S. Shenbagavalli; JPraveen Kumar; K. Semmanaselvan; Durai Swarna (The Egyptian Journal of Otolaryngology, 2024)
Abstract Background Tracheal stenosis results from an altered inflammatory response to mucosal damage, which leads to impairment of breathing and can even be fatal if not treated promptly (Ind J Otolaryngol Head Neck Surg 73(4):447–454, 2020). ENT and head and neck surgeons face difficulties while treating tracheal stenosis. Mechanical stress from extended endotracheal intubation or tracheostomy, combined with hypoxic metabolic disturbances during an underlying event, is the most frequent cause of tracheal stenosis (Al-Azhar Int Med J 3(10):149-57, 2022). The main objective of the study is to assess the outcomes of tracheal resection and anastomosis in patients who presented with tracheal stenosis. This emphasizes the need for proper case selection and timely surgical intervention to relieve the airway obstruction and to ensure the effectiveness of tracheal resection and anastomosis as the less morbid approach by avoiding a midline sternotomy. The study was conducted in a tertiary care center on 25 patients who were admitted in ENT ward from the year 2011 to year 2021. Case records of those patients who underwent tracheal resection and anastomosis were analyzed on a retrospective basis. Detailed history taking and clinical examination with appropriate investigations like flexible bronchoscopy, computed tomography with 3-dimensional reconstruction, video laryngoscopy, direct laryngoscopy, and lung function tests were carried out for all the patients in the study as required. An evaluation of GERD was also done. Appropriate surgical procedure was done with regular post-operative follow-up for 18 months. Results In our study, 92% of patients had satisfactory outcomes following tracheal resection and anastomosis, while some patients experienced minor complications. In 8% of patients, the primary surgery failed, among whom one patient underwent revision surgery and is doing well. The other patient with post-traumatic stenosis with a long stenotic segment underwent Shiann Yann Lee procedure in an outside center which resulted in failure following which T tube insertion was done. The patient showed improvement and was decannulated after a month. In our study of 25 patients with tracheal stenosis, postoperative complications occurred and were managed accordingly. However, there was no significant correlation between these complications and patient age, sex, extent of stenosis, preoperative Cotton-Myer grading, or the type of surgical procedure performed. This lack of correlation may be attributed to the limited sample size. Conclusion Tracheal resection and anastomosis are challenging procedures and should be done only in centers with experience. Standard treatment consists of resection of the stenotic segment with end-to-end anastomosis. The geometry of the ends to be anastomosed is matched properly to avoid gaps or weak points and for air-tight seal anastomosis.